BERBAGAI ALTERNATIF PENDEKATAN PSIKOLOGIS DALAM STUDI AGAMA - Wardani, Wardani (Jurnal Ilmiah Ilmu Ushuluddin, 2016)
This article is aimed to describe psychological approaches in the study of religions. Psychology provides many perspectives, such as Feudian psychoanalysis, eventhough it considered religion as pathology, also provided semantic tool to understand inner religious experiences. Another side of psychoanalysis functioned to study the development of children?s religious experiences. Psychology also can be applied to study spiritual awakening, or more precisely, conversion from non-religious into religious experience, or from situation to other one. Trans-personal psychology is more concerned with therapeutic practices, but in the view of Dan Merkur, this kind of psychology should be called as ?theology? rather than psychology in true sense of the word.